Experiences of Living With Primary Progressive Aphasia: A Scoping Review of Qualitative Studies. (20th January 2020) - Davies, Katharine; Howe, Tami
Introduction: Understanding the experiences of people who live with primary progressive aphasia (PPA) can inform the development of appropriate speech-language pathology services for this population. This review aimed to summarize the qualitative research on the experience of living with PPA from the perspective of the individuals with the disorder and their families. Methods: A scoping review was conducted. Results: Eight studies met the inclusion criteria. Themes in the 3 investigations that focused on the individual's perspective included adapting to overcome language difficulties and dealing with increased dependency. Themes identified in the 5 studies that highlighted the family's perspective included observing and adapting to language, behavioral, and social communication changes; lack of awareness of PPA; control; and the impact of the historical relationship. Discussion: Experiences from the 2 perspectives differed. Further research is needed, particularly in relation to identifying the general experience of PPA from the perspective of individuals with the disorder.